Determining the Effect of a High Fructose Diet on Interscapular Brown Adipose Tissue LPL, Cellularity and Lipid Deposition in Aging Congenic Obese-T2DM Rats - Tulp, Orien L (Contemporary Research and Perspectives in Biological Science Vol. 2, 2024)
The present study aimed to determine the effect of a high fructose diet on brown adipose tissue development in aging congenic obese T2DM rats. The physiological merits of brown adipose tissue (BAT) metabolism as an efficient potential energy buffer that when deficient, may be a contributor to excess fat accretion and to the development of obesity in man and animals. As such, it offers to be a potential target for therapies that could be developed for its treatment. To determine the effects of dietary fructose consumption on development and cellularity of brown adipose tissue in T2DM, groups of lean and obese SHR/Ntul//-cp rats demonstrating insulin resistance (IR) and heritable T2DM were fed diets containing 54% (w/w) carbohydrate as cornstarch (CS diet) or equal parts CS plus fructose (CSF diet) plus essential proteins, fats, vitamins, minerals, and dietary fiber from one to nine months of age. The SHR/Ntul//-cp rat is a congenic animal model in which the only genetic difference between the phenotypes is the epigenetic inheritance and natural expression of the obese (-cp) trait, which is distinct from dietary, toxicologic, or pharmacologic factors and is accompanied by the development of chronic insulin resistance (IR) and non-insulin-dependent diabetes (T2DM) shortly after weaning in the obese phenotype. The effects of this study indicate that final weight gain and Interscapular brown adipose tissue mass and cellularity are significantly greater in the obese than in the lean phenotype. In addition, the effects of a high fructose diet resulted in only modest increases in body weight gain, and in differential effects on IBAT cellularity and cell lipid content. Weight gain of obese >> lean and was greater when fed the CSF than the CS diet in both phenotypes; Interscapular brown adipose tissue (IBAT) mass of obese >> Lean and was similar in both phenotypes. IBAT Mass: Body weight of Obese >> lean, and trended greater in lean CSF vs CS but less in Obese CSF vs CS. IBAT cell size and lipid content of obese >> lean, and the CS vs CSF diet was similar in lean but decreased in the obese phenotype. IBAT cell number of obese >>> lean, while IBAT cell number of lean CSF > lean CS, but IBAT cell number of obese was similar with both diets. Lipoprotein lipase activity (LPL) of lean >> obese and trended to be greater with the CSF than the CS diet in both phenotypes and IBAT tissue lipid content of obese >> lean with a trend toward CSF > CS in both phenotypes. These results indicate that IBAT development occurs via hyperplasia and hypertrophy in the Obese phenotype of this strain and that long term consumption of the high Fructose diet enhances IBAT cellularity in the lean phenotype while the IBAT cellularity was maximally enhanced by both diets in the obese phenotype. These results further indicate that the impact of long-term consumption of a high fructose diet throughout much of the natural lifespan impacts the development of IBAT mass and cellularity differentially in the lean and obese+T2DM phenotype, likely at least in part due to contributions of longstanding IR in the obese+T2DM animals. Because IR is known to impede cellular glucose uptake in isolated brown adipocytes as an essential process in the expression of cellular thermogenic responses, any potential mechanisms to override or bypass the process or decrease the magnitude of IR would be presumed to exert a beneficial effect. Fructose may increase the potential for the expression of IBAT development and the expression of non-shivering thermogenesis in response to changes in food and environment because it can enter tissues independently of insulin activities, for example, through the GLUT1 and GLUT5 transporters. Nevertheless, in the current investigation, it was discovered that overall fructose consumption was neither significantly advantageous nor ameliorative in resolving crucial parameters of brown adipose tissue expression as contributors to the development of obesity in the obese+T2DM phenotype.